The degradation and utilization of formaldehyde-treated urea by rumen microbes in vitro - Setälä, Jouko; Syrjälä-Qvist, Liisa (Agricultural and Food Science, 1982)
Urea was treated with different levels of formaldehyde (HCHO). The HCHO percentages, on a weight basis, were 0(F0), 0.25 (F0.25) 0.50 (F0.50), 0.75 (F0.75), 1.0 (F1.0), 1.5 (F1.5), 2.0 (F2.0), 3.0 (F3.0) and 5.0(F5.0). Twenty milligrams of urea was incubated for 5 hours in 40 ml of sheep rumen fluid-buffer solution (1:1) together with 1.5 grams of substrate. The substrate consisted of vacuum-dried and milled feeds: barley (25 %), molassed beet pulp (25 %) and NaOH-treated straw (50 %). The feeds and urea were used in the same proportions as in the diet of the sheep which yielded the rumen fluid for incubation. Treatment with HCHO decreased hydrolysis of urea to ammonia. The ammonia concentration in contents offer mentors 2 hours after the start of incubation had a highly significant (P < 0.001) negative correlation (r = -0.976, n = 72) with the HCHO treatment level. Microbial protein synthesis was calculated from tungstic acid - sulphuric acid precipitation. Synthesis of protein, expressed as grams of nitrogen per 100 grams fermented organic matter was highest when F1.5-F3.0 urea was used. Treatment with more than 3 % of HCHO decreased the number of protozoa and the general activity of the microbes, thus decreasing fermentation of organic matter and lowering the yield of microbial protein. When F1.5 urea was used, the total yield (mg protein/hr) was significantly higher than with untreated urea, but the results obtained with F1.5 urea did not differ significantly from those with F0.75 or F2.0 urea.